Soil-transmitted helminthiasis among indigenous communities in Malaysia: Is this the endless malady with no solution? - Mohd-Shaharuddin, Norashikin; Lim, Yvonne Ai Lian; Hassan, Nur Amirah; Nathan, Sheila; Ngui, Romano (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Soil-transmitted helminths (STHs) are the most common intestinal parasitic infections of medical importance in human. The infections are widely distributed throughout the tropical and subtropical countries including Malaysia particularly among disadvantaged and underprivileged communities. This study was conducted to determine the prevalence and pattern of STH infections among Temuan indigenous subgroup. A cross sectional study was conducted among five villages in Peninsular Malaysia. Faecal samples and socioeconomic data were collected from each consented participant. Faecal samples were processed using formalin-ether sedimentation and examined under microscope. Data analysis was carried out using SPSS software programme for Windows version 24. A total of 411 participants voluntarily participated in this study. The overall prevalence of STH infections was 72.7% (95% CI = 68.2 – 77%). The most common STH species recorded was Trichuris trichiura (58.4%, 95% CI = 53.5 – 63.2%) followed by Ascaris lumbricoides (45.5%, 95% CI = 40.6 – 50.5%) and hookworm (23.1%, 95% CI = 19.1 – 27.5%). Multivariate analysis demonstrated that using untreated water was a significant predictor of STH infections in these communities. Our findings demonstrated that STH infections are still prevalent and co-exist with the low SES among this subgroup. Poverty and poor sanitation are the leading factors contributing to this malady. Hence, the reassessments of the existing control measures are needed.